2010
DOI: 10.1167/iovs.09-4483
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Visualization and Analysis of Parafoveal Capillaries in Humans

Abstract: Using motion cues to enhance vessel contrast is a powerful tool for visualizing the capillary network, in the absence of contrast agents. The authors demonstrate a tool to study the microcirculation of healthy subjects noninvasively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
173
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 22 publications
9
173
0
4
Order By: Relevance
“…However, there is no convincing evidence to support these differences. [21][22][23] Another predictor of better anatomical response to laser treatment is the morphological subtype of the oedema on OCT. The morphological categories of our Qualitative and quantitative OCT response to macular laser photocoagulation R Vemala et al cohort with diffuse macular oedema showed that 57% were DRT, whereas 37% were cystoid in keeping with the observations of Brar et al 24 On correlating the angiographic and OCT appearance of DMO, they observed that angiographic evidence of diffuse macular oedema is most often associated with DRT on OCT, although microcysts are common, whereas cystoid leakage on fluorescein angiography is always associated with cystic changes on spectral domain OCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no convincing evidence to support these differences. [21][22][23] Another predictor of better anatomical response to laser treatment is the morphological subtype of the oedema on OCT. The morphological categories of our Qualitative and quantitative OCT response to macular laser photocoagulation R Vemala et al cohort with diffuse macular oedema showed that 57% were DRT, whereas 37% were cystoid in keeping with the observations of Brar et al 24 On correlating the angiographic and OCT appearance of DMO, they observed that angiographic evidence of diffuse macular oedema is most often associated with DRT on OCT, although microcysts are common, whereas cystoid leakage on fluorescein angiography is always associated with cystic changes on spectral domain OCT.…”
Section: Discussionmentioning
confidence: 99%
“…23,33 Recently, parafoveal capillaries were visualized with advanced video processing techniques in AOSLO. 34 These motion contrast methods use the change in reflectance caused by blood flowing through the vessels (that is, the variance in the image) to map vessel paths. Tam et al 34 have shown that this technique can reveal the smallest vessels in a way that is superior to conventional fluorescein angiography and with vessel resolution that is comparable to that seen using FAOSLO.…”
Section: Retinal Vasculaturementioning
confidence: 99%
“…34 These motion contrast methods use the change in reflectance caused by blood flowing through the vessels (that is, the variance in the image) to map vessel paths. Tam et al 34 have shown that this technique can reveal the smallest vessels in a way that is superior to conventional fluorescein angiography and with vessel resolution that is comparable to that seen using FAOSLO. 21,33 The greatest advantage of this method over fluorescein angiography is that this technique can be done non-invasively and repeatedly, in both normal and diseased eyes.…”
Section: Retinal Vasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…Motion contrast perfusion maps were then generated to highlight the parafoveal capillary network. This motion contrast technique is similar to what was used by Tam et al [19], but with the AOSLO focus set at the plane of the retinal vasculature using multiply scattered light imaging [17] rather than at the plane of the photoreceptors for direct visualization of BCA movement and more precise rendering of the vessel lumen boundaries. Ten frames with the largest intensity variations were selected from the 50 frame video to calculate the perfusion map on a pixel-by-pixel basis.…”
Section: Image Processing and Luminal Surface Reconstructionmentioning
confidence: 99%